"3PL" Service Improvement Opportunities in Transport Companies. (2017) - Batarlienė, Nijolė; Jarašūnienė, Aldona
Abstract: The article reports the results of investigation of "3PL" areas, which has to be improve. The goal of this article is to present the results of research of "3PL" influence for company and to select key factors, which they have the influence to affect the business development. There are two main reasons then the managers should think about "3PL" service use: 1) the company is in decline, there are problems which are difficult or impossible to resolve only with internal resources; 2) the company is up and looking for additional opportunities for improvement. There is the analysis of the sources is made in order to state criteria of the "3PL" improvement problems in transport companies. According to the summed assessment scores a "3PL" service improvement opportunities affecting criteria list is generated. The priority queue is based on the number of points that were given for each criterion; it is expressed as a percentage of their significance. Following a survey of experts, received kits of estimation are processed statistically. Is used the pairwise comparison method. By ranking method, significance of indicators is identified by direct means. Following the survey, there are received ratings of respondents. Respondents' reliability of the assessment is expressed by concordance coefficient of opinions characterizing the degree of overlap of individual opinions. Findings of research of "3PL" service providers are evaluated by eight factors (cost reduction, operational parameters, the use of information technology systems, flexibility, quality management, collaboration with customers, fixed assets and performance evaluation) as the most significant independent criteria, showing the importance. The result of the paper is a model designed and based on the analysis and criteria chosen by expert on "3PL" services that work for the improvement.